Increasing Literacy Movement Through Community of Practitioners 24 (KP-24) - Rahmah Purwahida (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2021)
The formation of a community of practitioners in this activity is relevant to advancing the literacy movement in Indonesia. The Community of Practitioners 24 (KP-24) empowers the cultivation of character education, environmental education, and family education through the literacy movement. The method of implementing this literacy movement activity is program planning, program implementation, and evaluation. In carrying out this activity, the community building team partnered with expert trainers of the Mobilizing School Program and the GAIN-IETTI Global TESOL Academy organization. The formation of the Community of Practitioners 24 (KP-24) to gradually spread the literacy movement throughout Indonesia through various programs initiated in this activity and will continue to be carried out regularly and systematically. Keywords: Community of Practitioners 24 (KP-24), literacy, GAIN-IETTI Global TESOL Academy Abstrak Pembentukan komunitas praktisi dalam kegiatan ini relevan untuk memajukan gerakan literasi di Indonesia. Komunitas Praktisi 24 (KP-24) memberdayakan penanaman pendidikan karakter, pendidikan lingkungan, dan pendidikan keluarga melalui gerakan literasi. Metode pelaksanaan kegiatan gerakan literasi ini yaitu perencanaan program, pelaksanaan program, dan evaluasi. Dalam pelaksanaan kegiatan ini, tim pembentukan komunitas bermitra dengan para pelatih ahli Program Sekolah Penggerak yang dan organisasi GAIN-IETTI Global TESOL Academy. Pembentukan Komunitas Praktisi 24 (KP-24) untuk menyebarluaskan gerakan literasi ke seluruh Indonesia secara bertahap melalui berbagai program yang diinisiasi dalam kegiatan ini dan akan terus dilanjutkan secara berkala dan tersistem. Kata kunci: Komunitas Praktisi 24 (KP-24), literasi, GAIN-IETTI Global TESOL Academy